Aspek-aspek yang Terabaikan dalam Pendaftaran Tanah Desa Adat di Bali - Utama, Tody Sasmitha Jiwa; Sari, Almonika Cindy Fatika (Undang: Jurnal Hukum, 2024)
This article examines the Comprehensive Systematic Land Registration (Pendaftaran Tanah Sistematis Lengkap, PTSL) program in Bali, Indonesia, amidst minimal state acknowledgment of adat land rights. Over a brief three-year period (2017-2019), PTSL successfully registered nearly a hundred thousand plots of customary village land. However, this accomplishment is not without its complexities and challenges. Conflicts arise among land rights holders concerning the continuity of possession and utilization, generating tensions between customary villages and their members (krama). Although these conflicts do not escalate into prominent turmoil, they illuminate crucial aspects overlooked in PTSL implementation. The first aspect highlights the neglect of diversity among adat land rights holders and variations in derivative rights (usufruct) beyond villages. The second underscores the disregard for meaningful consultation processes, neglecting to address disparities in land ownership within the customary system and imbalanced power relations within villages. The third aspect emphasizes that, despite efforts to establish tenurial certainty between residents and adat villages, the principal tenurial challenges lie in relationships between adat villages and the tourism industry and state projects. In conclusion, while PTSL achieves its primary goal of registering adat land, this article argues that pursuing the certainty of rights, without putting empirical diversity and complexity into account, may inadvertently lead to unforeseen uncertainties in the field. Abstrak Di tengah minimnya realisasi pengakuan negara atas hak masyarakat adat atas tanah di Indonesia, Pendaftaran Tanah Sistematis Lengkap (PTSL) di Bali justru berhasil mendaftarkan hampir seratus ribu bidang tanah desa adat dalam waktu kurang dari tiga tahun. Namun demikian, upaya ini tidak lepas dari dinamika dan tantangan. Pelaksanaan PTSL atas tanah desa adat diwarnai dengan kebingungan mengenai status kepemilikan tanah hingga keberlanjutan penguasaan dan pemanfaatan pasca pendaftaran. Kendati tidak sampai menimbulkan gejolak yang menonjol, konflik semacam ini mengindikasikan adanya aspek-aspek penting yang terabaikan dalam pelaksanaan PTSL. Aspek yang pertama adalah keragaman subjek pemegang hak adat selain desa adat dan pemegang hak turunan (guna pakai) atas tanah adat. Kedua diabaikannya proses konsultasi yang bermakna untuk merespon ketimpangan karakter penguasaan tanah dalam sistem adat dan negara. Aspek ketiga, pensertipikatan tanah desa adat di Bali lebih banyak diarahkan untuk memberikan kepastian relasi tenurial antara desa adat dan warganya sendiri. Padahal ancaman tenurial yang masif justru dibawa oleh ekspansi industri pariwisata dan proyek pembangunan negara. Pada akhirnya, kepastian hak yang menjadi tujuan pendaftaran dan sertipikasi tanah adat ini justru dapat menghasilkan rangkaian ketidakpastian ketika kompleksitas di lapangan terabaikan.